2003
DOI: 10.1002/yea.1032
|View full text |Cite
|
Sign up to set email alerts
|

Screening for new yeast mutants affected in mannosylphosphorylation of cell wall mannoproteins

Abstract: We have carried out a screen of 622 deletion strains generated during the EUROFAN B0 project to identify non-essential genes related to the mannosylphosphate content of the cell wall. By examining the affinity of the deletants for the cationic dye alcian blue and the ion exchanger QAE-Sephadex, we have selected 50 strains. On the basis on their reactivity (blue colour intensity) in the alcian blue assay, mutants with a lower phosphate content than wild-type cells were then arranged in groups defined by previou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
28
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 116 publications
4
28
1
Order By: Relevance
“…Moreover, given that the addition of the core of N-linked sugars to CPY is not affected in ecm33D, we suggest that the defect is probably in the Nlinked outer chain. In agreement with our results, ecm33D cells have lowered levels of sugar-linked phosphate at the cell surface (Conde et al, 2003). Conde et al (2003) identified a variety of mutants with altered mannosylphosphate content in the cell wall which define genes acting in different cellular processes, suggesting that several pathways may be involved in modulating the amount of mannosylphosphate in the cell wall.…”
Section: Discussionsupporting
confidence: 91%
“…Moreover, given that the addition of the core of N-linked sugars to CPY is not affected in ecm33D, we suggest that the defect is probably in the Nlinked outer chain. In agreement with our results, ecm33D cells have lowered levels of sugar-linked phosphate at the cell surface (Conde et al, 2003). Conde et al (2003) identified a variety of mutants with altered mannosylphosphate content in the cell wall which define genes acting in different cellular processes, suggesting that several pathways may be involved in modulating the amount of mannosylphosphate in the cell wall.…”
Section: Discussionsupporting
confidence: 91%
“…The function of other members of the MNN4 gene paralog family is unknown; however, knockout of one of these genes during the initial phase of this study (orf19.5557; this represents the second most similar ORF to the S. cerevisiae MNN4 gene sequence by FASTA analysis with an E value of 10 Ϫ7 and contains significant conservation of domain order with the budding yeast protein) in the strain CAI4 background had the result of partially lowering total Alcian blue binding (Table 3, strain CA-DSH5). This result was not unexpected, however, as a recent survey of 622 nonessential S. cerevisiae deletion strains found that approximately 10% showed alterations in Alcian blue binding (11), concluding that many diverse cellular pathways can ultimately contribute to the amount of cell wall mannosylphosphate.…”
Section: Resultsmentioning
confidence: 83%
“…Expression of MNN4 increases in late-logarithmic and stationary growth phases [32,33] . It has been shown that YJR061W is a putative membrane protein involved in glycosylation, and it has been shown to be repressed by Rim101p [34,35] . Further studies are needed to verify whether CaIPF14030 is involved in mannosylphosphorylation or glycosylation.…”
Section: Discussionmentioning
confidence: 99%